The uninsured and Medicaid Oregon tobacco user experience in a real world, phone based cessation programme. Issue 1 (1st March 2003) - El-Bastawissi, Ay; McAfee, T; Zbikowski, S M; Hollis, J; Stark, M; Wassum, K; Clark, N; Barwinski, R; Broughton, E
Abstract : Objective: To describe the experience of uninsured and Medicaid Oregon tobacco users who registered in Free & Clear (F&C), a telephone based cessation programme including five scheduled outbound calls. Design and setting: Using a retrospective cohort design, 1334 (423 uninsured, 806 Medicaid, and 105 commercially insured) Oregon tobacco users who registered in F&C between 18 November 1998 and 28 February 2000 were identified and followed for 12 months post-registration; 648 (48.6%) were successfully contacted at 12 months. Information was collected from the F&C database. Unconditional logistic regression, adjusted for race and education, was used. Results: The seven day quit rate at 12 months, assuming non-respondents were smokers, was 14.8% (95% confidence interval (CI) 13.0 to 16.9). This rate was significantly higher among commercially insured participants ( v Medicaid but not uninsured) and among participants who completed ⩾ 5 calls ( v < 5 calls). The quit rate for those contacted at 12 months was 30.6% (95% CI 27.0% to 34.3%) and varied, however not significantly, by insurance and number of calls. After adjustment, respondents who completed ⩾ 5 calls were 60% more likely to quit tobacco (odds ratio (OR) 1.6, 95% CI 0.9 to 3.1), and uninsured respondents who completed ⩾ 5 calls were 70% more likely to quit tobacco (OR 1.7, 95% CI 0.9 to 3.5), relative to those who completed < 5 calls, but the difference was not significant. Conclusions: The quit rates are similar to those reported in efficacy trials. The observed variation in quitting tobacco for respondents by number of calls completed and by insurance merits further investigation concentrating on increasing compliance with the call schedule, particularly for the uninsured.